Innovative potential of the enterprises as base of its development - Полозова, Т. В.; Кисліченко, А. П. (ХНУРЕ, 2021)
Innovation potential is the engine of effective movement and development of the enterprise in a changing business environment as well as a tool to ensure competitiveness in the market. Based on the analysis, the innovation potential of the enterprise is proposed to mean a set of interconnected resources, interaction and use of which provide the opportunity to effectively implement innovations, progressive development, efficiency and competitiveness of the enterprise under external and internal factors.
DOI: 10.30837/978-966-659-334-7
Keywords: innovative; innovative capital; innovative potential